Perception towards factors influencing transfer of training :a case study in Komag usa (Malaysia) sdn. (Sarawak Operation), Kuching - Wong, Lee Lee. (Universiti Malaysia Sarawak, UNIMAS, 2007)
The purpose of this study is to identify the various factors influencing transfer of training in Komag USA (Malaysia) Sdn. (Sarawak Operation), Kuching. This study also aims to determine the dominant factors influencing transfer of training. A set of questionnaire was used as the research instrument and was distributed to 161 respondents. The respondents in this study consisted of all the technical staff who had attended the Team Communication Training in Komag. The feedback collected was then analyzed by using Statistical Package for Social Sciences 14.0 (SPSS 14.0). Pearson Correlation Analysis was us ed to find out the significant relationship between transfer of training and transfer factors such as motivation to transfer, training design and transfer climate. The Stepwise Multiple Regression Analysis was used to determine the dominant factors influencing transfer of training. The outcome of this study shows that all the transfer factors studied in this research were found to have a positive significant relationship with transfer of training. Motivation to transfer and training design were identified as the dominant factors influencing transfer of training. Thus, based on the findings of this study, suggestions are made on how to improve the trainees’ motivation to transfer and training design to facilitate transfer of training.